A zero-based cultural perspective on dealing with the hybrid reality of teaching in business schools - FOURNIER, Susan (Institutional Knowledge at Singapore Management University, 2022)
Susan Fournier and Howard Thomas explore a new business school future, question existing approaches and identify and examine five core issues.